Effect of Magnetic Water and Phosphorus Rates on Some Nutrients Uptake by Summer Squash Grown In Calcareous Soil of Duhok Governorate. - Sarwar M. R. Ahmed (Science Journal of University of Zakho, 2015)
This study was conducted at the college of Agriculture/ Duhok University during August-November 2009, to study the effect of magnetic water treatment and phosphorus fertilizer rates (P0= 0, P1= 90, P2 = 180, P3 = 270) kg P2O5 ha-1 and their interactions on some nutrient uptake by summer squash plant in addition to their effect on some chemical properties soil at (0-15 and 15-30 cm) depth. Mulla-Ahmed seeds were sown in ridges 0.5 m apart. Half of the treatments were irrigated with well water and the other half with the same water after magnetization. The results indicated that magnetic water significantly increased dry weight of plants and also had significant effect on uptake of nutrients by plant and soil nutrients and they were significantly higher at 0-15 cm. An interaction of P3 x MW gave best uptake values by plant for most nutrients, higher concentration of calcium, magnesium, total nitrogen and phosphorus in the soil.